2019
DOI: 10.3346/jkms.2019.34.e164
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Fracture in Patients with Acute Ischemic Stroke in Korea

Abstract: Background Patients who survive an acute phase of stroke are at risk of falls and fractures afterwards. However, it is largely unknown how frequent fractures occur in the Asian stroke population. Methods Patients with acute (< 7 days) ischemic stroke who were hospitalized between January 2011 and November 2013 were identified from a prospective multicenter stroke registry in Korea, and were linked to the National Health Insurance Service claim database. The incidences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 47 publications
3
16
1
Order By: Relevance
“…Based on the Korean population-based hip-fracture study This study was consistent with previous reports indicating that the HD group had the highest IR of fractures among all ESKD patients 2,3,7,12 . Thus, we reinforced the significance of KRT modality as a risk factor for fracture in the presence of other comorbidities and specific medications 4,7,8,10,[12][13][14][15] . Based on our data, further attention is needed to prevent fractures in dialyzed patients, especially those on HD.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Based on the Korean population-based hip-fracture study This study was consistent with previous reports indicating that the HD group had the highest IR of fractures among all ESKD patients 2,3,7,12 . Thus, we reinforced the significance of KRT modality as a risk factor for fracture in the presence of other comorbidities and specific medications 4,7,8,10,[12][13][14][15] . Based on our data, further attention is needed to prevent fractures in dialyzed patients, especially those on HD.…”
Section: Discussionsupporting
confidence: 66%
“…We may presume that patients who survived after stroke are at high risk of falls and fractures. Indeed, patients with stroke carried a fourfold increased risk of fracture compared with healthy population 15 . Furthermore, patients with chronic lung disease are more likely to experience fractures, considering the use of inhaled corticosteroids or oral steroids, and their disability to ambulate leading to disuse osteoporosis and fragility fractures 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in BMD after stroke have reportedly been correlated with age, degree of paralysis, duration of paralysis, blood calcium level, vitamin D concentration, and vitamin K concentration during the first year, and degree of paralysis and blood vitamin D concentrations after two years [ 21 ]. The risk of fractures increases after a stroke; in particular, FN fracture occurrence is 2–4 times higher in stroke patients compared with the general population of the same age [ 4 , 5 ]. As such, stroke patients are more likely to develop osteoporosis, which increases the incidence of spine or FN fractures, which in turn increases the length of hospital stay and medical expenses.…”
Section: Discussionmentioning
confidence: 99%
“…Bone loss begins immediately after stroke, continues until 3–4 months after onset, and progresses at a slower rate until one year after onset [ 3 ]. Stroke patients fall frequently due to paralysis and loss of balance, and as a result, femur fractures are 2–4 times more common [ 4 , 5 ]. Most fractures after stroke occur in the hemiplegic side of the body because the BMD in this side decreases by 4.6–14% compared with the unaffected side [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Death rates from stroke rise sharply with age, and fractures increase the risk of death for stroke survivors. People who have a stroke are reported to have an approximately four‐fold increased risk of fracture compared to healthy people 3 . A previous study showed that fractures after ischemic stroke in mice exacerbate stroke‐induced neurological impairment and behavioral deficits, indicating that post‐stroke fractures can aggravate stroke damage to the body 4 .…”
Section: Introductionmentioning
confidence: 99%